2012
DOI: 10.1051/0004-6361/201014160
|View full text |Cite
|
Sign up to set email alerts
|

The slowly declining type Ia supernova 2008fv and the near-infrared second maximum

Abstract: Aims. We present optical and near-infrared (NIR) photometry of supernova (SN) 2008fv and a brief investigation of SN type Ia to search for possible correlations between the properties of NIR light curves and the optical decline rate. Methods. We analyse our BVRI and JHK observations to derive light curves (LCs), colour curves, and the bolometric behaviour of SN 2008fv. Data range from about five days before to two months after maximum. We also collect a database of the main characteristics of NIR LCs of SNe Ia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 73 publications
(81 reference statements)
4
14
1
Order By: Relevance
“…The correlation of M2 with ∆m15 is rather weak (Fig. 11) although it appears somewhat stronger than in Biscardi et al (2012) (the Pearson coefficients in our data are 0.5 and 0.63 for J and H compared to 0.12 and 0.08 in Biscardi et al 2012).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…The correlation of M2 with ∆m15 is rather weak (Fig. 11) although it appears somewhat stronger than in Biscardi et al (2012) (the Pearson coefficients in our data are 0.5 and 0.63 for J and H compared to 0.12 and 0.08 in Biscardi et al 2012).…”
Section: Discussioncontrasting
confidence: 51%
“…In parameterising the NIR light curves we follow the nomenclature introduced by Biscardi et al (2012). The first maximum in filter X, M1(X) is reached at a phase, t1(X) relative to the phase of the B maximum (t max B =0 d).…”
Section: Nir Light Curve Morphologymentioning
confidence: 99%
“…15). (Biscardi et al 2012), PS1-10w (Rest et al 2014). For objects with no optical data or bad MLCS fits with reduced χ 2 > 3, t Bmax is estimated from any or all of: the MJD of the brightest point (rounded to the nearest day), optical spectra in listed CBET/IAUC/ATEL notices, and cross checked with fitted phases of NIR LC features, where possible (see F12).…”
Section: Comparing Cfair2 and Csp Lcsmentioning
confidence: 99%
“…Recent studies (e.g. Biscardi et al 2012;Dhawan et al 2015) found that more luminous SNe Ia reach the second maximum in NIR filters at a later phase. This was predicted by Kasen (2006), who also indicated that the phase of the second maximum (designated in the following as t 2 and measured relative to the B-band light curve maximum) should be a function of the 56 Ni mass in the explosion.…”
Section: Introductionmentioning
confidence: 99%